Mapping of Karst Areas and Ethnographic Studies Local Communities of Lisabata - Nurlaila Sopamena; Fany Aljihad; Ikhsan Hambali; Hazli Alfadli; Muhammad Zaky Ghifary; Muhammad Kashai Ramdhani Pelupessy; Fadli Fendi Malawat (IAIN AMBON, 2022)
This paper aims to identify the potential of karst areas as a material for consideration in the management of sustainable karst areas through the process of collecting data and mapping the existence of caves and the potential of the local community of Lisabata through ethnographic studies, especially exploring the role of women in the management and utilization of social, cultural and environmental potentials. ; pioneering local community assistance maps to follow up on management plans and utilization of social, cultural and environmental potentials, especially karst areas; conducting an educational process, namely knowledge transfer and capacity building for local governments and community groups to manage and utilize karst areas; and provide input for the development of karst areas to village or regional governments that are oriented towards nature conservation and the welfare of local communities. The methods used in this ethnographic study were participatory observation, in-depth interviews, and FGD and PRA. The instruments used were Interview Instruments, Goa Susur Wearpack, Jumar Ascender Petzl, Helm Petzl, Superavanti Seat Harness Petzl, Croll Ascender, Laser Distance, Suunto Tandem Clinometer, Handy Talkie. As a result, there were five caves that were successfully mapped, namely the Tenin cave. Tutu'u, Mana'un Mahapeka, and Alaeke and Nian caves are recommended for geotourism